A REVIEW OF ENVIRONMENT & ENERGY FOR SUSTAINABLE CONSTRUCTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Today's impact on environment such as ozone depletion, green house effect and global warming and increased use of available natural resources for the energy consumption in the sector of building construction. This paper discussed on availability of such efficient services for the sustainable constructions. Also, it reviewed on the different development alternatives in sector of building construction for the cleaner energy consumed technology by the use of renewable or green energies like wind, solar energy, and biomass plants for the economic environment. In turn, this all impact on the humans life.